ANALISIS STRATEGI KOMUNIKASI KRISIS MIXUE DALAM MENANGGAPI ISU SERTIFIKASI HALAL: STUDI PADA MIXUE BANGBARUNG BOGOR - Amirah Inas; Suparman; Riyanto, Sutisna; Dharmawan, Leonard; Widia Khairunisa, Anggi; Putri Awalina, Salwa (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The food and beverage sector is currently in demand and growing rapidly in various parts of the world, including Indonesia as a country with a majority Muslim population. One of them is Mixue, a franchise that offers ice cream and fresh tea drinks. However, in mid-2022, social media was busy discussing information about Mixue not having a halal certificate. This raised public concerns and reduced consumer interest. This study aims to analyze the crisis communication strategy of the Mixue Bangbarung Bogor branch using the Situational Crisis Communication Theory (SCCT) and identify the obstacles and solutions applied. The research method uses a descriptive qualitative approach with data collection techniques of observation, interviews, literature studies, and document analysis. The results of the study show that Mixue Bangbarung implemented a diminishing strategy by acknowledging the issues circulating and providing clarification, as well as a rebuild strategy by optimizing social media and interactions with consumers. The Mixue Bangbarung Halal Certification issue was resolved directly by the owner because they did not have a special crisis communication team. Although there are consumers who do not have a problem with this issue, Mixue Bangbarung still experiences obstacles in the form of consumer doubts and concerns. The solution taken by Mixue Bangbarung is to routinely disseminate information and improve services to consumers. These strategies and solutions helped Mixue Bangbarung maintain its image and consumer trust and reduce the negative impacts of the crisis.